2016
DOI: 10.1186/s12967-016-0844-6
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical exploration of combining plasmacytoid and myeloid dendritic cell vaccination with BRAF inhibition

Abstract: BackgroundMelanoma is the most lethal type of skin cancer and its incidence is progressively increasing. The introductions of immunotherapy and targeted therapies have tremendously improved the treatment of melanoma. Selective inhibition of BRAF by vemurafenib results in objective clinical responses in around 50 % of patients suffering from BRAFV600 mutated melanoma. However, drug resistance often results in hampering long-term tumor control. Alternatively, immunotherapy by vaccination with natural dendritic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
8
2
Order By: Relevance
“…As described earlier, the use of immune checkpoint inhibitors in combination with a BRAF inhibitor + MEK inhibitor appears to be effective but is associated with a high rate of toxicity [ 194 ]. Other potential immune-targeted therapies undergoing preclinical investigation include adoptive T-cell therapy [ 171 , 248 , 249 ], dendritic cell vaccination [ 250 ], and combining BRAF inhibitor treatment with a toll-like receptor 7 agonist (e.g., imiquimod) [ 160 ].…”
Section: Resultsmentioning
confidence: 99%
“…As described earlier, the use of immune checkpoint inhibitors in combination with a BRAF inhibitor + MEK inhibitor appears to be effective but is associated with a high rate of toxicity [ 194 ]. Other potential immune-targeted therapies undergoing preclinical investigation include adoptive T-cell therapy [ 171 , 248 , 249 ], dendritic cell vaccination [ 250 ], and combining BRAF inhibitor treatment with a toll-like receptor 7 agonist (e.g., imiquimod) [ 160 ].…”
Section: Resultsmentioning
confidence: 99%
“…Here we chose the markers CD80, PDL-1, and CD40 (Figure 1A–1C ) as representatives for the maturation state of these DC subsets. CD80 is a co-stimulatory maturation marker also used in our clinical set up to determine the maturation state of the DCs [ 8 , 39 ]. PD-L1 as a co-inhibitory and CD40 as an additional co-stimulatory marker were considered suitable candidates to complete the set, because both maturation markers are known to be expressed on both cell subsets [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies VEM [ 20 ] and DAB [ 21 ] were reported to yield no immuno-modulatory effects on human MODC. Interestingly, Tel and coworkers [ 22 ] showed that VEM, but not DAB interfered with R848-induced upregulation of surface activation markers and cytokines by human primary DC. However, the inhibitiory effect of VEM on DC activation was largely prevented when applying VEM to total PBMC.…”
Section: Discussionmentioning
confidence: 99%